THE PRINCIPLES OF SOCIAL JUSTICE FUNCTION ON THE INDONESIA HEALTH SOCIAL ASSURANCE - S. Zanariyah, A. Suryono, M.N. Imanullah, A. Sulistiyono (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Every developing country must realize that development is carried out fairly for the benefit of the entire community by providing social security including guarantees in the health sector through social insurance. This paper examines the juridical review of the need to function the principle of justice in health insurance programs managed by the Health Insurance Agency (BPJS) Health and how to function the principle of social justice in the implementation of social security in the health sector. This research is included in the type of doctrinal research by carrying out a normative juridical approach, collecting data through literature studies sourced from primary legal materials, secondary legal materials and tertiary legal materials, then analyzed qualitatively. The results of the study show that the functioning of the principle of justice in the implementation of social security in the health sector is carried out as the implementation of legislation in the field of health insurance by providing equal protection to all citizens, not only those who are able to pay contributions, but also apply to people who do not able, whose contribution is paid by the government, through the mechanism of social insurance in the health sector.